2015
DOI: 10.1111/petr.12426
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus‐associated smooth muscle tumors in children following solid organ transplantation: A review

Abstract: EBV-SMT are a rare entity following organ transplantation. Given the rarity of the tumor, there is no standard approach to diagnosis and treatment. A literature search identified 28 reported cases of EBV-SMT in addition to our own experience with one case. The aim of this review is to summarize the existing data regarding pathogenesis, diagnosis, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 38 publications
6
55
0
1
Order By: Relevance
“…6 A few cases occurring in the adrenal glands have been reported. 7 In contrast, PT-SMT occurs preferentially in the liver, 8 lungs/ larynx/pharynx, gut, spleen, and kidneys, sometimes in the brain, and rarely in the adrenal gland and the iris of the eye. 9 Very few cases of congenital immunodeficiency disorderassociated SMT have been reported, and lungs/larynx are most frequently affected, followed by intracranial tumors, liver, adrenal, and spleen.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A few cases occurring in the adrenal glands have been reported. 7 In contrast, PT-SMT occurs preferentially in the liver, 8 lungs/ larynx/pharynx, gut, spleen, and kidneys, sometimes in the brain, and rarely in the adrenal gland and the iris of the eye. 9 Very few cases of congenital immunodeficiency disorderassociated SMT have been reported, and lungs/larynx are most frequently affected, followed by intracranial tumors, liver, adrenal, and spleen.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, unlike in somatic SMT, where the malignant behavior and clinical outcome are predicted by the histologic features, the behavior of EBV-SMTs does not correlate well with their histologic features and apparent grade of lesion. 6,8 Some of the well-differentiated tumors devoid of mitoses and atypia have proven to be lethal. 3 Thus, it has been proposed that these tumors be designated as SMT of uncertain potential.…”
Section: Histopathologic Featuresmentioning
confidence: 99%
“…EBV involvement using in situ hybridization for EBV-encoded small RNA (EBER) confirmed the diagnosis of EBV-SMT in all reports. Association with PTLD is common, ranging from 38-82% (18,19). Although PTLD was the working diagnosis at the time of appendiceal surgery, to date no PTLD has been identified in our patient.…”
Section: Discussionmentioning
confidence: 84%
“…The lack of prior EBV immunity may additionally contribute to the higher mortality rate in children (18). A review by Jossen et al found a female predominance of EBV-SMTs following solid organ transplantation (21 female patients and only 8 male patients) (19). Most EBV-SMTs are multifocal at the time of diagnosis, with some occurring in sites with little smooth muscle, such as the dura, spleen, tonsils, and glottis (6,20).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric transplant recipients, who are usually EBV-naïve and immunosuppressed, are at much higher risk of developing PTLD following an acute EBV infection. However, transplant recipients can also develop other, rarer forms of EBV-associated malignancies, such as smooth muscle tumors (1), which are poorly described in the literature. Here, we present the case of a pediatric liver recipient who developed an acute illness that was initially suspicious for PTLD, until the surprising diagnosis of lymphoepithelial carcinoma (LEC) was made.…”
Section: To the Editorsmentioning
confidence: 99%